Surface Enhanced Electrochemiluminescence Immunoassay for Highly Sensitive Detection of Disease Biomarkers in Whole Blood. Issue 8 (13th April 2016) - Yang, Runping; Liu, Yuanlin; Ye, Huazhen; Qiu, Bin; Lin, Zhenyu; Guo, Longhua
Abstract: Recently we demonstrated that the localized surface plasmon resonance (LSPR) of noble metal nanoparticles would significantly enhance the electrochemiluminescence (ECL) emission of Ru(bpy)3 2+ . Based on this finding, we developed a new branch of surface enhanced spectroscopy (SES), namely, surface enhanced electrochemiluminescence (SEECL). In this communication, we demonstrate for the first time the combination of SEECL with conventional immunoassay technique to develop a new electroanalysis method called surface enhanced electrochemiluminescence immunoassay (SEECL‐IA). The proposed method is demonstrated for the detection of prostate specific antigen (PSA), and the results show that our method can detect as low as 2.0×10 −12  ng/mL PSA in whole blood without any sample pretreatment process. Abstract :